2022
DOI: 10.3390/ijerph192214861
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of the SMART Work & Life Intervention for Reducing Sitting Time

Abstract: Sedentary behaviours continue to increase and are associated with heightened risks of morbidity and mortality. We assessed the cost-effectiveness of SMART Work & Life (SWAL), an intervention designed to reduce sitting time inside and outside of work, both with (SWAL-desk) and without (SWAL-only) a height-adjustable workstation compared to usual practice (control) for UK office workers. Health outcomes were assessed in quality-adjusted life-years (QALY) and costs in pound sterling (2019–2020). Discounted co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…It is clear from these data that many of the clusters and participants in level 4 still implemented and engaged with various aspects of the intervention (as shown in Table 5 ). This suggests that a more pragmatic and less burdensome intervention may still be beneficial, and cost effective based on the behaviour change observed [ 19 ], for those workplaces/offices who are unable deliver and/or engage with all intervention components. For example, provision of a height-adjustable workstation with education may still yield meaningful behaviour change even without other strategies offered in the present intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear from these data that many of the clusters and participants in level 4 still implemented and engaged with various aspects of the intervention (as shown in Table 5 ). This suggests that a more pragmatic and less burdensome intervention may still be beneficial, and cost effective based on the behaviour change observed [ 19 ], for those workplaces/offices who are unable deliver and/or engage with all intervention components. For example, provision of a height-adjustable workstation with education may still yield meaningful behaviour change even without other strategies offered in the present intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The main study was a three-arm cluster randomised controlled trial to evaluate the effectiveness of the SWAL sitting reduction intervention, delivered with and without a height-adjustable workstation. The main trial protocol has been described in detail elsewhere [ 18 ] along with the main effectiveness [ 15 ] and cost effectiveness results [ 19 ]. Ethical approval for the trial was received from the University of Leicester’s College of Life Sciences (Ref:14,372).…”
Section: Methodsmentioning
confidence: 99%
“…For example, correlative findings indicated that the more individuals perceived their supervisor as supportive of active breaks, the more likely they were to experience less sedentary time (Lafrenz et al 2018 ). Furthermore, one could compare the intervention components of Leicht Beweg t to components of other interventions such as the Stand More AT (SMArT) Work intervention or SMART Working and Life (SWAL) intervention that appear to be effective in the long term (Edwardson et al 2018 , 2022 ) but require more financial resources (Cox et al 2022 ).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…A lack of standardized and objectively determined outcome measures (Chu et al 2016 ) and an exclusive reliance on participants’ subjective reports (Prince et al 2020 ) pose main problems. Cost-effectiveness analyses of multicomponent interventions to reduce sedentary times at workplace further show that, although they are likely to pay off in the long run from a health economics perspective, they are associated with substantial initial costs to the employer—particularly if height-adjustable workstations need to be purchased (Cox et al 2022 ; Michaud et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%